2010
DOI: 10.1007/s10517-010-1090-1
|View full text |Cite
|
Sign up to set email alerts
|

Morphofunctional Characteristics of Syncytiotrophoblast and Content of Heat Shock Protein 70 in It during Exacerbation of Herpesvirus Infection in Pregnant Women

Abstract: Exacerbation of herpesvirus infection during pregnancy is associated with damage to syncytiotrophoblast inflicted by herpesvirus either directly or via TNF-α (due to contact of NK lymphocytes with villus surface). A sharp decrease in the content of heat shock protein with a molecular weight of 70 Da and activation of caspase-3 were noted in placenta homogenate. This leads to disturbances in syncytiotrophoblast cytosol structure and increase in the relative content of apoptotic nuclei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Low Hsp70 levels also corresponded with high caspase-3 levels and apoptotic nuclei. The findings suggest that the viral infection suppresses Hsp70 levels, thereby promoting caspase activation and apoptosis (Lutsenko et al 2010). It was also recently demonstrated that HSV-1 inhibits the unfolded protein response (UPR) during the early stages of infection of cultured human cells.…”
Section: Herpes Simplex Virusmentioning
confidence: 89%
See 1 more Smart Citation
“…Low Hsp70 levels also corresponded with high caspase-3 levels and apoptotic nuclei. The findings suggest that the viral infection suppresses Hsp70 levels, thereby promoting caspase activation and apoptosis (Lutsenko et al 2010). It was also recently demonstrated that HSV-1 inhibits the unfolded protein response (UPR) during the early stages of infection of cultured human cells.…”
Section: Herpes Simplex Virusmentioning
confidence: 89%
“…It was also recently demonstrated that HSV-1 inhibits the unfolded protein response (UPR) during the early stages of infection of cultured human cells. Viral inhibition of UPR frees the virus from fidelity control of protein synthesis and can increase the efficiency of viral replication 1,000-fold (Burnett et al 2012;Lutsenko et al 2010). Loss of UPR disrupts endoplasmic reticulum homeostasis and can thereby lead to a number of pathological sequelae (see below).…”
Section: Herpes Simplex Virusmentioning
confidence: 99%
“…Therefore, it can be postulated that elevated production of hsp70 may contribute to cell survival during placental and embryo development by the downregulation of whichever process, autophagy or apoptosis, is being activated. Interestingly, first-and third-trimester placentas that have become infected with herpesvirus manifest a decreased concentration of Hsp70 (Lutsenko et al 2010). Whether this potentiates destruction of the infected cells by apoptosis and/or is an attempt to remove the virus by induction of autophagy remains undetermined.…”
Section: Placental Developmentmentioning
confidence: 99%